Response of soybean lines to Soybean mosaic virus under drought stress - Wuye Ria Andayanie; Praptiningsih Gamawati Adinurani; Martin Lukito (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
The aim of this study was to assess soybean lines response to infection of Soybean mosaic virus (SMV) under drought stress. The experiment was conducted at the glasshouse in factorial in Randomized Complete Block Design (RCBD) with four replications. The first factor is soybean lines with four soybean lines (GK/PI, GK/M8Grb, W/M, GK/LT) including one susceptible check variety i.e. Anjasmoro. The second factor is drought stress with three levels of soil water content (100, 75, and 50%) field capacity. Seven days after planting (DAP), plants were inoculated with sap from leaves SMV infected soybean. The result showed that drought stress levels had affected the percentage of seed weight loss in GK/L-T than in the Anjasmoro variety. The number of leaves was slowly decreased from 42 to 49 DAP. The level, duration, and frequency of drought stress affected more significant in the inhibition of the seed filling phase. The GK/L-T reaction was not detected in the presence of SMV and also the lowest of Absorbance ELISA Value. The seed yield (t/ha) of GK/L-T that was most superior and the lowest percentage of disease severity under drought stress.